The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11255-018-1903-0
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node dissection in prostate cancer using superparamagnetic particles of iron oxide: early clinical experience

Abstract: SLND with SPION is feasible and safe in prostate cancer and the diagnostic accuracy is comparable to the published results of radioguided procedures. In open surgery, SPION may be used as an alternative tracer with its main advantage being the lack of radiation hazard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In a large patient dataset, it is now shown that a reduction down to half of the stipulated dose is highly effective and that a deeper preoperative injection yields more SLNs while retaining a high SPIO-RI concordance rate and resulting in less skin staining, when injected peritumorally. The use of SPIO in other clinical situations, such as SLN identification and dissection in malignant melanoma [31], prostate cancer [32][33][34], penile cancer [35] and uterine cancer [36], has been investigated, with interesting implementations.…”
Section: Discussionmentioning
confidence: 99%
“…In a large patient dataset, it is now shown that a reduction down to half of the stipulated dose is highly effective and that a deeper preoperative injection yields more SLNs while retaining a high SPIO-RI concordance rate and resulting in less skin staining, when injected peritumorally. The use of SPIO in other clinical situations, such as SLN identification and dissection in malignant melanoma [31], prostate cancer [32][33][34], penile cancer [35] and uterine cancer [36], has been investigated, with interesting implementations.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected from the included manuscripts accounted for a total of 2586 patients. Regarding SLN tracer selection, a total of 10 papers reported the use of technetium 99m-nanocolloids (99mTc-NC) [18,19,29,33,35,[37][38][39][40][41], 6 papers of "free" indocyanine green (ICG) [17,22,28,30,32,44], 3 papers of "hybrid" ICG-99mTC-NC tracer [23,24,31], 4 papers superparamagnetic of iron oxide nanoparticles (SPION) [25][26][27]36], 2 papers of PSMA radiotracer [20,21], 1 paper of technetium 99m-sulfur [34], 1 paper of technetium 99mphylate [42], and 1 paper of technetium 99m human serum albumine (HAS) [43]. Two groups combined the use of 99mTc-NC and intraoperative ICG within the same cohort [23,24].…”
Section: Diagnostic Outcomesmentioning
confidence: 99%
“…Two groups combined the use of 99mTc-NC and intraoperative ICG within the same cohort [23,24]. Regarding tracer administration, 11 papers reported an intraprostatic injection template [17][18][19]22,24,25,27,29,37,38,43]. Intra-/peri-lesional administration was performed in two reports [18,29].…”
Section: Diagnostic Outcomesmentioning
confidence: 99%
“…Staník et al showed that SPIONs could be used as an alternative to the gold standard to detect the SLN in intermediate and high risk PCa. They performed magnetometer-guided SLND gaining a diagnostic rate of 95% [11].…”
Section: Spions For Sentinel Lymph Nodementioning
confidence: 99%
“…In urologic oncology, SPIONs are injected in peritumoral or into the primary tumor for the identification of the sentinel lymph node (SLN) such as penile cancer and prostate cancer in all its variant [8,9]. Also, in BC could help identify SLN [10][11][12][13]. Despite all, SPIONs have an impact on the cellular viability in BC, hinder the neovascularization and induce autophagy in endothelial progenitor cells [14,15].…”
Section: Introductionmentioning
confidence: 99%